Radioluminescence imaging feasibility for robotic radiosurgery field size quality assurance. Issue 10 (24th August 2022) - Shakarami, Zahra; Broggi, Sara; Vecchio, Antonella Del; Fiorino, Claudio; Spinelli, Antonello E.
Abstract: Purpose: To investigate the feasibility of radioluminescence imaging (RLI) as a novel 2D quality assurance (QA) dosimetry system for CyberKnife®. Methods: We developed a field size measurement system based on a commercial complementary metal oxide semiconductor (CMOS) camera facing a radioluminescence screen located at the isocenter normal to the beam axis. The radioluminescence light collected by a lens was used to measure 2D dose distributions. An image transformation procedure, based on two reference phantoms, was developed to correct for projective distortion due to the angle (15°) between the optical and beam axis. Dose profiles were measured for field sizes ranging from 5 mm to 60 mm using fixed circular and iris collimators and compared against gafchromic (GC) film. The corresponding full width at half maximum (FWHM) was measured using RLI and benchmarked against GC film. A small shift in the source‐to‐surface distance (SSD) of the measurement plane was intentionally introduced to test the sensitivity of the RLI system to field size variations. To assess reproducibility, the entire RLI procedure was tested by acquiring the 60 mm circle field three times on two consecutive days. Results: The implemented procedure for perspective image distortion correction showed improvements of up to 1 mm using the star phantom against the square phantom. The FWHM measurements using the RLI system indicated a strong agreement with GC film with maximum absolute difference equal to 0.131 mm for fixed collimators and 0.056 mm for the iris. A 2D analysis of RLI with respect to GC film showed that the differences in the central region are negligible, while small discrepancies are in the penumbra region. Changes in field sizes of 0.2 mm were detectable by RLI. Repeatability measurements of the beam FWHM have shown a standard deviation equal to 0.11 mm. Conclusions: The first application of a RLI approach for CyberKnife® field size measurement was presented and tested. Results are in agreement with GC film measurements. Spatial resolution and immediate availability of the data indicate that RLI is a feasible technique for robotic radiosurgery QA.